Highly Efficient Nonradiative Energy Transfer from Colloidal Semiconductor Quantum Dots to Wells for Sensitive Noncontact Temperature Probing - Olutas, Murat (2017)
This study develops and shows highly efficient exciton-transferring hybrid semiconductor nanocrystal films of mixed dimensionality comprising quasi 0D and 2D colloids. Through a systematic study of time-resolved and steady-state photoluminescence spectroscopy as a function of the donor-to-acceptor molar concentration ratio and temperature, a high-efficiency nonradiative energy transfer (NRET) process from CdZnS/ZnS core/shell quantum dots (QDs) directed to atomically flat CdSe nanoplatelets (NPLs) in their solid-state thin films is uncovered. The exciton funneling in this system reaches transfer efficiency levels as high as 90% at room temperature. In addition, this study finds that with decreasing temperature exciton transfer efficiency is increased to a remarkable maximum level of ≈94%. The enhancement in the dipole–dipole coupling strength with decreasing temperature is well accounted by increasing photoluminescence quantum yield of the donor and growing spectral overlap between the donor and the acceptor. Furthermore, NRET efficiency exhibits a highly linear monotonic response with changing temperature. This makes the proposed QD–NPL composites appealing for noncontact sensitive temperature probing based on NRET efficiencies as a new metric. These findings indicate that combining colloidal nanocrystals of different dimensionality enables efficient means of temperature probing at an unprecedented sensitivity level at nanoscale through almost complete exciton transfer.